A SYSTEMATIC REVIEW ON SELF-MICRO EMULSIFYING DRUG DELIVERY SYSTEMS: A POTENTIAL STRATEGY FOR DRUGS WITH POOR ORAL BIOAVAILABILITY - Radha, G. V.; Sastri, K. Trideva; Burada, Sadhana; Rajkumar, Jampala (International Journal of Applied Pharmaceutics, 2019)
Currently a marked interest in developing lipid-based formulations to deliver lipophilic compounds. Self-emulsifying system has emerged as a dynamic strategy for delivering poorly water-soluble compounds. These systems can embrace a wide variety of oils, surfactants, and co-solvents. An immediate fine emulsion is obtained on exposure to water/gastro-intestinal fluids. The principal interest is to develop a robust formula for biopharmaceutical challenging drug molecules. Starting with a brief classification system, this review signifies diverse mechanisms concerning lipid-based excipients besides their role in influencing bioavailability, furthermore pertaining to their structured formulation aspects. Consecutive steps are vital in developing lipid-based systems for biopharmaceutical challenging actives. Such a crucial structured development is critical for achieving an optimum formula. Hence lipid excipients are initially scrutinized for their solubility and phase behavior, along with biological effects. Blends are screened by means of simple dilution test and are consequently studied with more advanced biopharmaceutical tests. After discerning of the principle formula, diverse technologies are offered to incorporate the fill-mass either in soft/hard gelatin capsules. There is also feasibility to formulated lipid-system as a solid dosage form. Although such solid technologies are desirable but such should not undermine the biopharmaceutical potential of lipid-formulations.